Nonlinear difference equations with asymptotically stable solutions - Slyusarchuk, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We establish conditions of asymptotic stability for all solutions of the equation X n+1=F(X n ), n≥0, in the Banach space E in the case where r(F′(x))